Hubungan Efikasi Diri dan Academic Burnout dengan Prestasi Belajar Siswa Kelas XI SMAK St. Albertus Malang - Anastasia Sherly Privana; Yuliati Hotifah; Diniy Hidayatur Rahman; Anastasia Sherly Privana; Yuliati Hotifah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: In the new normal era like today, learning in several schools uses a blended learning system. The existence of a new learning system causes changes, for example in student achievement. Several studies have shown that student achievement is influenced by various aspects, such as self-efficacy and academic burnout. This research was conducted with the aim of knowing the correlation between efficacy and academic burnout with the achievement of student learning outcomes in class XI in Senior High School St. Albertus Malang. The instrument was tested on 97 people with validity 0.329 and reliability 0.912 and 0.830. Based on the results found, there is a correlation between self-efficacy and academic burnout with learning achievement but not simultaneously or together. The correlation value that occurs is 0.045 or 4.5 percent and 95.5 percent is related to other variables outside the variables research. Abstrak: Pada era new normal seperti saat ini, pembelajaran di beberapa sekolah menggunakan sistem blended learning. Adanya sistem pembelajaran baru berdampak pada berbagai aspek salah satunya pada pencapaian hasil belajar peserta didik. Ditemukan bahwa hasil pembelajaran yang diraih individu dipengaruhi oleh berbagai aspek, misalnya efikasi diri dan academic burnout. Penelitian ini dilakukan dengan maksud mengetahui korelasi efikasi dan academic burnout dengan pencapaian hasil belajar siswa kelas XI di SMAK St. Albertus. Instrumen diujikan pada 97 orang dengan validitas 0,329 dan reliabilitas 0,912 serta 0,830. Berdasarkan hasil yang ditemukan, terdapat korelasi antara efikasi diri dan academic burnout dengan prestasi belajar namun tidak simultan atau bersama-sama. Nilai korelasi yang terjadi sebesar 0,045 atau 4,5 persen dan 95,5 persen berhubungan dengan variabel yang tidak diteliti.